Open Papers - Abstracts of Poster Presentations (Nepal Journal of Epidemiology, 2014)
Abstracts of the Poster Presentations at the Open Papers session at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10170